Dashboards to support rehabilitation in orientation and mobility for people who are blind - Moraes, José M. L.; Do Carmo F., Phyllipe; Araújo, Maria da C. Carneiro; Costa, Bernardo; Amorim, Myrna; Façanha, Agebson Rocha; dos Santos, Joel; Viana, Windson (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2023: Proceedings of the 29th Brazilian Symposium on Multimedia and the Web, 2023)
In Brazil, there are over 7 million individuals with visual disabilities (PDVs), including at least 500,000 blind individuals, according to IBGE 2019 data. Orientation and Mobility (OM) training is crucial for PDVs to navigate, identify objects, determine directions, and reach destinations. Existing literature offers virtual OM environments using gamification and Virtual Reality (VR) techniques. However, there is a lack of customizable maps and detailed monitoring of student interaction in these environments. This article proposes integrating game analytics and customization methods in OM teaching for PDVs. The main goal is to assist OM teachers in utilizing gamification and VR for safe and engaging practices. The integration aims to enhance customization, gamification, and monitoring, enabling better assessment of student progress and personalized activities to maximize engagement and learning.